Additional file 4: of West Nile virus infection and interferon alpha treatment alter the spectrum and the levels of coding and noncoding host RNAs secreted in extracellular vesicles - Slonchak, Andrii; Clarke, Brian; Mackenzie, Jason; Amarilla, Alberto; Setoh, Yin; Khromykh, Alexander (National Health and Medical Research Council, 2021)
Fil: Slonchak, Andrii. University of Queensland; Australia.